Forward guidance: A new challenge for central banks - Otmar Issing (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
In a contribution prepared for the Athens Symposium on 'Banking Union, Monetary Policy and Economic Growth', Otmar Issing describes forward guidance by central banks as the culmination of the idea of guiding expectations by pure communication. In practice, he argues, forward guidance has proved a misguided idea. What is presented as state of the art monetary policy is an example of pretence of knowledge. Forward guidance tries to give the impression of a kind of rule-based monetary policy. De facto, however, it is an overambitious discretionary approach which, to be successful, would need much more (or rather better) information than is currently available. In Issing's view, communication must be clear and honest about the limits of monetary policy in a world of uncertainty.
urn:nbn:de:hebis:30:3-343294
Keywords: 330; central bank communication; monetary policy; forward guidance